Magnesium Supplementation in Vitamin D Deficiency. (January 2019) - Reddy, Pramod; Edwards, Linda R.
Abstract : Background: Vitamin D and magnesium (Mg) are some of the most studied topics in medicine with enormous implications for human health and disease. Majority of the adults are deficient in both vitamin D and magnesium but continue to go unrecognized by many health care professionals. Areas of Uncertainty: Mg and vitamin D are used by all the organs in the body, and their deficiency states may lead to several chronic medical conditions. Studies described in the literature regarding these disease associations are contradictory, and reversal of any of these conditions may not occur for several years after adequate replacement. One should consider the supplementation therapy to be preventative rather than curative at this time. Data Sources: PubMed search of several reported associations between vitamin D and Mg with diseases. Results: Vitamin D and Mg replacement therapy in elderly patients is known to reduce the nonvertebral fractures, overall mortality, and the incidence of Alzheimer dementia. Conclusions: Vitamin D screening assay is readily available, but the reported lower limit of the normal range is totally inadequate for disease prevention. Based on the epidemiologic studies, ∼75% of all adults worldwide have serum 25(OH)D levels of <30 ng/mL. Because of the recent increase in global awareness, vitamin D supplementation has become a common practice, but Mg deficiency still remains unaddressed. Screening for chronic magnesium deficiency is difficult because a normal serum level may still be associated with moderate to severe deficiency. To date, there is no simple and accurate laboratory test to determine the total body magnesium status in humans. Mg is essential in the metabolism of vitamin D, and taking large doses of vitamin D can induce severe depletion of Mg. Adequate magnesium supplementation should be considered as an important aspect of vitamin D therapy.